The Statute of Limitation and its Applicability to Tax Matters - Agbonika, Josephine Aladi Achor (NIU Journal of Humanities, 2018)
The right to litigate is not usually everlasting and may be restricted by a statute of limitation which stipulates a period of time within which a claim may no longer be filed. If it is filed, it could be liable to be struck out if the defence to that claim is, or includes that, it is statute-barred as having been filed after the limitation period. The intention of these laws is to facilitate resolution of disputes within a reasonable length of time. This is predicated on the fact that legal proceedings are not meant to last in perpetuity. Thus, limitation period generally begins when the plaintiff’s cause of action accrues or when they become aware of the legal wrong or injury occasioned to them. Limitation of actions virtually covers almost all areas of litigation, but, for the purpose of this work, particular attention is paid to limitation of actions against tax matters.